COMBINATORIAL GAMES IN MATH LEARNING - HOW TO STUDY THEM IN THE COMPULSORY SCHOOL - Luminita Catana (National Centre for Policy and Evaluation in Education, 2013)
This paper proposes some mathematical games, simple and elegant, which can become activities that teachers can successfully use for the course "Game and movement" or in any math class. We have highlighted the main benefits of such activities for a child's personality development and, in particular, for his mental development. The article also warns that the playful methods, especially math games, are missing from the initial and continuous training of teachers.